Internalization of Indonesian Language as a Critical Thinking Development Effort in Character Formation - Andriany, Liesna (Universitas Malikussaleh, 2019)
Indonesian language courses are compulsory for every student. The purpose of this study is to describe the Indonesian language learning strategy by internalizing Indonesian language education in the development of critical thinking. Critical thinking criteria using FRISCO from Ennis. This research is qualitative with research instruments using observation, questionnaires, interviews, documentation, and tests. Whereas the data analysis technique following Miles and Huberman is done by data reduction and continuous data presentation. Data validity uses data triangulation. The findings show that the critical thinking skills of students on average meet the UISU National Standards. Development of a project-based Indonesian learning strategy that is tailored to the material. The process of internalizing Indonesian education emphasizes critical thinking skills in character building. Proven project-based Indonesian learning strategies can hone students' critical thinking skills so that student character education is formed.